COVID-19 and the kidney: what we think we know so far and what we don’t - Farouk, Samira S. (J Nephrol, 2020)
The novel coronavirus disease infection (COVID-19) outbreak that was declared a global pandemic in March 2020 had led to an internationally variable but concerning incidence of COVID-associated acute kidney injury (AKI), with prevalence reported as high as 46% in large cohorts of hospitalized patients. Variability in AKI may be explained by differences in traditional risk factors for AKI, heterogeneity among patient cohorts, and differences in racial and ethnic groups. Further, AKI requiring kidney replacement therapies (KRT) has been associated with increased mortality. Proposed mechanisms of kidney injury include direct viral-induced tubular or glomerular injury, sepsis-associated AKI, and thrombotic disease. Kidney pathology include acute tubular injury, glomerular fibrin thrombi, pigmented tubular casts, and collapsing focal segmental glomerulosclerosis. “Viral-like” particles have been observed in renal samples at electron microscopy and viral RNA has been identified in both glomerular and tubular compartments of kidney specimens, but the link between viral presence and injury remain unclear. Though the link between AKI and poor outcomes is clear, prevalence and outcomes of COVID-19 in patients with chronic kidney disease and end stage kidney disease has not yet been reported. In patients on immunosuppression like those with kidney transplants or glomerular disease, COVID-19 has presented a management dilemma. Herein, we review the existing literature on kidney disease in COVID-19 and discuss what remains to be learned.